The Influence of Social Media Marketing and Electronic Word of Mouth (E-WOM) on Brand Equity and Its Impact on Purchasing Decisions Case Studies on Briton English Education - Magfira Amalia; Haris Maupa; Dian Parawansa (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to determine the effect of Social Media Marketing on Brand Equity, the effect of Electronic Word of Mouth on Brand Equity, the influence of Brand Equity on Purchasing Decisions, the influence of Social Media Marketing and Brand, and the Electronic Word of Mouth. Purchase Decisions via Brand Equity as a variable. Intervention. This study uses a path analysis model. The sample in this study were 340 students of Briton English Education. The data in this study were obtained by distributing questionnaires. The results showed that the Social Media Marketing (X1), Electronic Word of Month (X2) variable had a significant effect on Purchasing Decisions (Z). This can be seen from the coefficient which is positive and the significance value is smaller than 0.05. The results also show that Social Media Marketing (X1), Electronic Word of Mouth (X2), and Brand Equity (Y) have a positive and significant effect on Purchasing Decisions (Z). This can be seen from the coefficient which is positive and the significance value is smaller than 0.05. In this study, it is also known that there is no mediating effect of the Brand Equity variable between the independent variables consisting of Social Media Marketing (X1) and Electronic Word of Mouth (X2) on the dependent variable of Purchase Decision (Z). This can be seen from the value of the indirect effect on the path coefficient which is smaller than the value of the direct effect.